Cocoa Canopy Replacement to Increase Productivity and Plant Resistance to Vascular Streak Dieback - Teguh Iman Santoso; Adi Prawoto; Sudarsianto Sudarsianto (Indonesian Coffee and Cocoa Research Institute, 2013)
Canopy replacement with vascular streak dieback (VSD) resistant clones is expected to reduce VSD infestation by reducing space of Oncobasidiumtheobromae infection, and to increase cocoa yield. This experiment was carried out in endemic areas of VSD in Kaliwining Experimental Station of ICCRI and Kendenglembu estate. Canopy replacement technique in Kendenglembu was done by side cleft grafting on primary branches and top grafting on plagiotropic branches of primary branches. Number of grafted shoots per plant, i.e. 1, 2, 3, 4, 5 and 6 was used as treatments using Sca 6 and Sulawesi 1. The 12 treatments were arranged in randomized complate block design, each treatment replicated 6 times and 10 plants per treatment. Growth of shoot, canopy coverage and development of VSD incidence were the main variables. In Kaliwining, side cleft grafting was applied at 1.5 m above soilsurface using Sulawesi 1 and Sca 6 clones as the scion and TSH 858 and ICS 60 clones as rootstocks. VSD intensity was observed by scoring method. Cocoa yield was the main variable. The result showed that both techniques caused similar growth rate of the shoots. The rate of canopy covering by resistant clones reduced VSD infestation following Y = -0.7848X + 69.324 (R² = 0.995) equation. Three resistant shoots per tree was effective in reducing VSD infestation. Four years after grafting were bean yield by using Sulawesi 1 was 434% over control while 360% yield for Sca 6 compared to average control of ungrafted plants of ICS 60 and TSH 858. Polyphenol content of both resistant clones was higher than that on susceptible ones, however transfer mechanism of that substance to the susceptible stocks is still unknown. It is concluded that canopy replacement using productive and resistant clones is considered to be an effective method to overcome VSD problem and to improve cocoa yield. Key words:Theobroma cacao, vascular streak dieback, canopy replacement, yield.